Audit Energi Pada Gedung Terminal Petikemas Makassar (TPM) PT Pelabuhan Indonesia IV - Mattangang, Apollo; Rahman, Abdul; Aditya Putrawan, Alif; Stephanie, Debby; Ekagracestelyn, Ekagracestelyn (Jurnal Teknik Mesin Sinergi, 2025)
Abstract. An energy audit is a systematic activity that involves observation, recording, measurement, and assessment of a building’s energy use with the aim of identifying potential energy savings. This study aims to calculate energy consumption and evaluate potential savings at the Makassar Container Terminal (TPM) Building of PT Pelabuhan Indonesia IV, specifically on the first and second floors. The audit was conducted on the building envelope, lighting system, and air-conditioning system. The research methodology included literature review, field survey, data collection, and analysis of energy consumption using the indicators of Energy Use Intensity (EUI) and Overall Thermal Transfer Value (OTTV). The results indicate that the building falls into the efficient category, with average EUI values for air-conditioned spaces of 9.45 kWh/m² on the first floor and 9.08 kWh/m² on the second floor. Furthermore, the OTTV value of the building envelope was 25.32 W/m², which remains below the standard limit set by SNI at 35 W/m². Therefore, this energy audit demonstrates that the TPM Building complies with energy efficiency standards for buildings and can serve as a reference for the implementation of sustainable energy management.